Isolasi dan Identifikasi Endomikoriza Indigenus pada Perakaran Salak di Kabupaten Karangasem dan Perbanyakannya - DIPUTRA, I MADE MARTANA; RAI, I NYOMAN; DHARMA, I PUTU (Agrotrop : Journal on Agriculture Science; Vol 8 No 1 (2018)DO - 10.24843/AJoAS.2018.v08.i01.p07, 2018)
Isolation and Identification of Endomycorrhizal Indigenous on Salak Rhizosphere in Karangasem Regency and its Propagation. This research aimed to determine and obtain AMF indigenus isolates and their propagation at different levels of soil water content. This research used Completely Randomized Design with 2 Factors. The first factor was location of soil sampling, consisting of 3 levels of treatment (Location 1, Location 2, and Location 3) and the second factor was soil water content consisting of 3 levels of treatment (100, 70, and 40% field capacity). The results of isolation and identification indicate that there were two genus of AMF found on salak rizosphere in Karangasem Regency, those were Glomus and Gigaspora with several different species in it. The percentage of root infection rate was 100% and was categorized very high. The result of AMF spore propagation showed that combination treatment of location 1 which sandy clay soil textured and 40% field capacity produced the highest spores i.e 2382 spores or rised 2282% from 100 spores which were inoculated.